N-terminal engineering of glutamyl-tRNA reductase with positive charge arginine to increase 5-aminolevulinic acid biosynthesis. Issue 4 (4th July 2017) - Zhang, Junli; Weng, Huanjiao; Ding, Wenwen; Kang, Zhen
ABSTRACT: Five-Aminolevulinic acid (ALA), the universal precursor of all tetrapyrroles, has various applications in medicine and agriculture industries. Glutamyl-tRNA reductase (GluTR) as the first key enzyme of C5 pathway is feedback regulated by heme, and its N-terminus plays a critical role on its stability control. Here, the GluTR N-terminus was engineered by inserting different numbers of positively charged lysine and arginine residues. The results confirmed that insertion of lysine or arginine residues (especially one arginine residue) behind Thr2 significantly increased the stability of GluTR. By co-expression of the GluTR variant R1 and the glutamate-1-semialdehyde aminotransferase, ALA production was improved 1.76-fold to 1220 mg/L. The GluTR variant R1 constructed here could be used for engineering the C5 pathway to enhance ALA and other products.